2001
DOI: 10.1007/s003830100604
|View full text |Cite
|
Sign up to set email alerts
|

Functional outcome after pyeloplasty for unilateral ¶symptomatic hydronephrosis

Abstract: The functional outcome and factors influencing improvement after pyeloplasty for ureteropelvic junction (UPJ) obstruction are still debated. This retrospective study was aimed at evaluating the factors associated with functional improvement in symptomatic unilateral hydronephrosis (HDN). Patients (n = 68) who underwent successful pyeloplasty for unilateral symptomatic UPJ obstruction without any other associated urological abnormality were included. Preoperative evaluation included a diuretic renogram (DR) to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
39
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 0 publications
5
39
0
Order By: Relevance
“…We showed that the overall DRF and SKGFR were significantly improved after relief of obstruction. The same findings have been reported in a pediatric population [12,13]. …”
Section: Discussionsupporting
confidence: 76%
“…We showed that the overall DRF and SKGFR were significantly improved after relief of obstruction. The same findings have been reported in a pediatric population [12,13]. …”
Section: Discussionsupporting
confidence: 76%
“…Among symptomatic patients, Chandrasekharam et al. [27] found a significantly greater improvement in patients presenting with a mass, and Calisti et al. [35] similarly in those diagnosed with crossing vessels.…”
Section: Resultsmentioning
confidence: 99%
“…Assuming that the earlier the obstruction is released the better the function after surgery [9], it might also seem logical that the younger the patient at surgery the better the resulting function. Eight studies analysed the effect of age at surgery on final DRF [7,11,14,15,17,24,27,31]. Seven reported that age does not affect the eventual functional outcome for both prenatal and postnatal HN [7,11,14,15,17,24,31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have attempted to determine functional outcomes after pyeloplasty according to the timing of surgery, but the results of these studies were often conflicting. Chandrasekharam et al [11] reported that infants <1 year of age showed significant improvement in renal function after pyeloplasty compared with older children. In their study, differential renal function recovered to the near normal range (>40%) in the early surgery group.…”
Section: Discussionmentioning
confidence: 99%